The Effect of Carbon Emission Disclosure on Firm Values with Environmental Performance and Media Exposure as a Moderating Variable - Hartina Husein; Paul Usmany; Tiara Tiara (Pattimura Proceeding, 2026)
This study aims to examine the effect of carbon emission disclosure on firm value, and to determine whether environmental performance and media exposure moderates these relationships. Using a quantitative approach with secondary data form annual reports and sustainability reports, this research employs Moderated Regression Analysis test the hypotheses. The sample consist of 20 companies from carbon-intensive sectors (energy, industry and transportation). Firm value is measured using Tobin’s Q, carbon emission disclosure by a dummy variable, environmental performance by ISO 14001 certification, and media exposure by dummy coding of media coverage. Result finding that carbon emission disclosure has a significant positive effect on firm value, but media exposure does not significantly moderate the relationship between carbon disclosure and firm value. This study supports signaling theory and legitimacy theory confirming carbon disclosure serves as a positive signal to investors and enhances corporate legitimacy. It also extends the understanding of stakeholder influences in emerging markets like Indonesia. Interestingly, while environmental performance strengthens this relationship, media exposure does not, suggesting in the Indonesian context, formal certification is more credible than media narratives.